2022
DOI: 10.3390/pharmaceutics14122713
|View full text |Cite
|
Sign up to set email alerts
|

Silk-Elastin-like Polymers for Acute Intraparenchymal Treatment of the Traumatically Injured Spinal Cord: A First Systematic Experimental Approach

Abstract: Despite the promising potential of hydrogel-based therapeutic approaches for spinal cord injury (SCI), the need for new biomaterials to design effective strategies for SCI treatment and the outstanding properties of silk-elastin-like polymers (SELP), the potential use of SELPs in SCI is currently unknown. In this context, we assessed the effects elicited by the in vivo acute intraparenchymal injection of an SELP named (EIS)2-RGD6 in a clinically relevant model of SCI. After optimization of the injection system… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 109 publications
0
2
0
Order By: Relevance
“…The ELR genes were synthesized following recombinant DNA technologies, and the protein recombinamers were produced using the Escherichia coli expression system as previously described [ 30 , 31 ]. The ELRs were purified from the bacterial biomass by several cycles of temperature-dependent reversible precipitation [ 32 ].…”
Section: Methodsmentioning
confidence: 99%
“…The ELR genes were synthesized following recombinant DNA technologies, and the protein recombinamers were produced using the Escherichia coli expression system as previously described [ 30 , 31 ]. The ELRs were purified from the bacterial biomass by several cycles of temperature-dependent reversible precipitation [ 32 ].…”
Section: Methodsmentioning
confidence: 99%
“…Conductive hydrogels with nanoparticles ( Yang et al, 2022 ) or nanosheets ( Chen et al, 2022 ) following stimulated spinal cord injury demonstrated decreases in GFAP-labeled astrocytes, as well as decreases in chondroitin sulfate proteoglycans and increased neuronal markers ( Table 2 ). Studies using nanofiber hydrogels (NFH) have shown different outcomes, with NFH alone demonstrating no induction of astrocytes ( Gonzalez et al, 2022 ), while increased amounts of astrocytes at the injury site were seen using an NFH construct combined with BMSCs ( Li et al, 2020 ; Haggerty et al, 2022 ). Nanoparticle hydrogel composites have also shown varying results ( Serafin et al, 2022 ).…”
Section: Nanomaterials For Api Delivery To Cns Gliamentioning
confidence: 99%